Use of Erythropoiesis-Stimulating Agents in the Treatment of Anemia in Patients With Systolic Heart Failure. (January 2015) - Lindquist, Desirae E.; Cruz, Jennifer L.; Brown, Jamie N.
Objective: To determine the efficacy and safety of erythropoiesis-stimulating agents (ESAs) for the treatment of anemia in patients with systolic heart failure. Data Sources: A search of MEDLINE (1946-January 2014) and EMBASE (1947-January 2014) was conducted using the search terms erythropoietin and systolic heart failure. In addition, bibliographies of relevant articles were reviewed for additional citations. Study Selection and Data Extraction: All English language randomized controlled trials evaluating clinical outcomes or adverse events when using ESAs in the setting of systolic heart failure were included. Data Synthesis: A total of 9 studies were reviewed. All studies examining hematological parameters found a statistically significant increase in hemoglobin levels with active treatment versus placebo. Of the 7 trials evaluating exercise tolerance or capacity, only 4 demonstrated statistically significant improvement in these measures in patients receiving ESAs, whereas the remainder showed no clinical benefit. Four studies examined quality-of-life measures. Although numerical improvements were observed in most trials, statistical significance was reached in only 2 trials. A nonsignificant trend for decreased mortality in patients treated with darbepoetin with a similar adverse event profile compared to placebo was shown in one study; however, the largest trial to date showed no benefit in all-cause mortality or heart failure-related hospitalizations with the use of ESAs. Additionally, a statistically significant increase in the number of cerebrovascular events and thrombotic events was found. Conclusion: There is inconclusive evidence to suggest that the use of ESAs in treating anemia in patients with heart failure is beneficial. Although ESAs demonstrated a clear ability for increasing hemoglobin levels, the data regarding clinical outcomes such as exercise parameters, quality of life, and hospitalizations are conflicting. In addition, a mortality benefit has not been shown; therefore, the potential for improved symptomatology must be weighed against the potential for adverse events.